Equilibrio entre vida laboral y vida familiar de los colaboradores en la empresa de capacitaciones profesionales “CASCEP” - Cordones Cordones, Adriana Rocío (2024)
This research aimed to determine the existing balance between work and family life of the collaborators in the Professional Training Company "CASCEP". For this purpose, a descriptive and analytical research based on a quantitative approach was used; to support the study, the analysis of similar studies that argued theoretically and directed the research was carried out; it is also worth mentioning that the study was strengthened with the collection of data using the Work-Family Reconciliation Questionnaire CTF/CFT designed by the author Carlson, Kacmar and Williams in 2000, which measures the work-family balance and whose reliability level is 0.87, in such a way that it was applied to the population of 63 people who work for the company, 44,44% and 49.21% of the workers show a work-family conflict at a high and medium level respectively, showing prevalence in conflicts due to the time they dedicate to work, stress, exhaustion, and pressure at work that absent them from family activities and responsibilities, making the behaviors they develop at home inefficient to solve problems at work, which makes them less productive. Consequently, it was concluded that there is no balance between the work and family life of the collaborators hindered by time, stress and behavior that negatively affect these environments. For this reason, the study proposed strategies that motivate companies to establish good working practices that encourage the transformation of the organization with flexible conditions, alternatives to reduce stress, exhaustion, and work fatigue and provide support to employee in the process of improving their family behaviors that limit them at work.